1987
DOI: 10.1056/nejm198710083171502
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Papillomavirus-Associated Penile Intraepithelial Neoplasia in Sexual Partners of Women with Cervical Intraepithelial Neoplasia

Abstract: To determine whether neoplastic cervical lesions in women are associated with papillomavirus infections in their sexual partners, we used a colposcope to examine male sexual partners of women with cervical flat condyloma (294 cases) or cervical intraepithelial neoplasia (186 cases), before and after 5 percent acetic acid was applied to the penis and the anogenital area. Condylomata acuminata, papules, and macules were observed in 309 of the 480 men (64.4 percent). In 204 of them (42.5 percent), macules or slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
127
0
22

Year Published

1989
1989
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(160 citation statements)
references
References 26 publications
7
127
0
22
Order By: Relevance
“…Human papillomavirus has also been linked to cancers of the vulva, vagina, anus, and penis (IARC 1995;Melbye and Frisch, 1998). Genital HPV types are transmitted sexually and the risk of infection has been associated with numerous parameters involving sexual behaviour (Franco et al, 1995;Bosch et al, 1996;Kjaer et al, 2001).Partner studies have shown that penile lesions are found in more than half of the male partners of women with cervical intraepithelial neoplasia (CIN) (Barrasso et al, 1987;Campion et al, 1988;Hippelainen M et al, 1991;Bleeker et al, 2002). Flat lesions are reported as the most prevalent lesion type and their relationship with HPV has been established (Barrasso et al, 1987;Campion et al, 1988;Hippelainen M et al, 1991;Hippelainen MI et al, 1993b;Bleeker et al, 2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Human papillomavirus has also been linked to cancers of the vulva, vagina, anus, and penis (IARC 1995;Melbye and Frisch, 1998). Genital HPV types are transmitted sexually and the risk of infection has been associated with numerous parameters involving sexual behaviour (Franco et al, 1995;Bosch et al, 1996;Kjaer et al, 2001).Partner studies have shown that penile lesions are found in more than half of the male partners of women with cervical intraepithelial neoplasia (CIN) (Barrasso et al, 1987;Campion et al, 1988;Hippelainen M et al, 1991;Bleeker et al, 2002). Flat lesions are reported as the most prevalent lesion type and their relationship with HPV has been established (Barrasso et al, 1987;Campion et al, 1988;Hippelainen M et al, 1991;Hippelainen MI et al, 1993b;Bleeker et al, 2002).…”
mentioning
confidence: 99%
“…Flat lesions are reported as the most prevalent lesion type and their relationship with HPV has been established (Barrasso et al, 1987;Campion et al, 1988;Hippelainen M et al, 1991;Hippelainen MI et al, 1993b;Bleeker et al, 2002). Since flat penile lesions are only well visible after acetowhitening, their presence remains often unnoticed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HPV DNA has been found in invasive cancers (Durst et al, 1983;zur Hausen, 1984;McCance et al, 1985;Grubb, 1986), pre-invasive lesions (Walker et al, 1984;Campion et al, 1985;De Villiers et al, 1987) and has been found to be related to progression of disease (Campion et al, 1986). Promiscuity in men has also been linked to increased risk in their sexual partners (Buckley et al, 1981;Zunzunegui et al, 1986) and recent studies have shown that males harbour human papilloma virus in penile lesions Villa & Lopes, 1986) and that sexual partners share increased risk of genital cancer (Kessler, 1976;Smith et al, 1980;Barrasso et al, 1987).…”
mentioning
confidence: 99%
“…Também já se considerou que o efeito protetor da circuncisão seja não propriamente em relação ao HIV, mas sim em relação a outras IST, em especial as que cursam com úlcera peniana, e que, estas sim, estariam diretamente associadas ao HIV. 37 Szabo & Short 41 consideram que o epitélio estratificado, escamoso e queratinizado dos circuncidados proporciona uma barreira de proteção ao HIV, ao passo que a superfície 6 32 A maior susceptibilidade de incircuncisos ao carcinoma peniano parece ser resultado da ação do vírus do papiloma humano. 30 A presença do prepúcio também seria um fator facilitador ao surgimento de câncer de cérvice uterina em parceiras sexuais de incircuncisos.…”
Section: O Prepúcio E As Origens Da Circuncisão Masculinaunclassified